A university for the 21st century - Duderstadt, James J., 1942- (University of Michigan Press, 2000)
From the former president of one of America's leading universities comes a comprehensive analysis of the challenges and opportunities facing higher education in America as we enter the twenty-first century. In A University for the 21st Century, James J. Duderstadt discusses the array of powerful economic, social, and technological forces that are driving the rapid and profound change in American social institutions and universities in particular.Change has always characterized the university as it has sought to preserve and propagate the intellectual achievements, the cultures, and the values of our civilization. However, the capacity of the university to change, through a process characterized by reflection, reaction, and consensus, simply may not be sufficient to allow the university to control its own destiny. Not only will social and technical change be a challenge to the American university, Duderstadt says, it will be the watchword for the years ahead. And with change will come unprecedented opportunities for those universities with the vision, the wisdom, and the courage to lead in the twenty-first century. The real question raised by this book is not whether higher education will be transformed, but rather how ... and by whom.